Analysis of the influence of leadership style and organizational culture on employee performance of PT Sraya Dinamika Mandiri - Rizkiana Karmelia Shaura; Hendra Kurniawan; Yulianah, Yulianah (Jurnal Ekonomi, 2024)
In order for a business to realize its organizational objectives, the best way to get there is for employees to perform well in their jobs. However, because it encompasses all of an organization's existing stakeholders, human resource management in any given company is not an easy task. In order for the goals of the company to be accomplished, it is necessary to have an appropriate organizational culture as well as an appropriate leadership style. The purpose of this study is to investigate the relationship between PT Sraya Dinamika Mandiri's organizational culture and leadership styles as they relate to employee performance. This research method is a quantitative descriptive method with a population of 48 participants with random sampling. The findings of the study indicate that there is a positive and significant relationship between leadership style and organizational culture in terms of the impact it has on organizational performance, both individually and jointly. With the findings in this study, top managers at PT Sraya Dinamika Mandiri are able to develop corporate policies that can preserve indicators of leadership style and organizational culture.